Calcium ions affect sludge digestion performance via changing extracellular polymeric substances in anaerobic bioreactor. (June 2020) - Ma, Haitong; Guo, Chenyan; Yao, Min; Wu, Ming; Wang, Zhiwei; Wang, Shuangfei
Abstract: In this study, batch tests were conducted with and without the addition of calcium ions to clarify the interaction between calcium ions and extracellular polymeric substances (EPS). The maximum degradation rates of EPS and chemical oxygen demand (COD) in the reactor with the addition of Ca 2+ reached 58.26, 67.19, 69.35 mg∙g −1 mixed liquor suspended solids (MLSS) and 89.70%, 94.04%, 91.70%, respectively, and were higher than those in the control reactor. The results showed that Ca 2+ (1000–2000 mg∙L −1 ) significantly promoted the secretion of EPS and improved sludge digestion performance during the process of anaerobic digestion. In addition, Ca 2+ changed the functional groups of EPS and the microstructure of granular sludge compared with the control reactor. The concentrations of EPS in the reactor with added Ca 2+ were positively correlated with the COD degradation rate, with coefficients of determination of 0.88, 0.91, and 0.98 in reactors R1, R2, and R3, respectively, which suggests that EPS can affect the bioactivity of anaerobic granular sludge (AnGS), and particularly the degradation of organics. The results were reaffirmed by analyzing volatile fatty acids (VFAs) and cytochrome c (c-Cyts). There was no obvious relationship between the EPS content and COD degradation rate in the control reactor (R 2  = 0.63), which indicates that Ca 2+ may be an important factor in attaining the above results. Therefore, we speculate that Ca 2+ caused changes in EPS, as the concentration of EPS increased and the COD degradation rate increased (and vice versa ), which affected the digestion performance of AnGS. Highlights: Ca 2+ promoted the secretion of EPS and improved sludge digestion performance. EPS content is positively correlated with the degradation rate of COD. Ca 2+ affect sludge digestion performance via changing EPS.